menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
(-8 (-8x+20) = -8(-*-3) Step 1: -6x +15 = 8x + 24 Step 2:15 = 2x + 24 Step 3: -9 = 2x Step 4: x==
asked
Jun 1, 2023
67.4k
views
23
votes
(-8
(-8x+20) = -8(-*-3)
Step 1: -6x +15 = 8x + 24
Step 2:15 = 2x + 24
Step 3: -9 = 2x
Step 4: x==
Mathematics
high-school
Blearn
asked
by
Blearn
4.8k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
13
votes
Answer:
-9/2
Explanation:
Divide both sides of the equation by 2.
Per Salbark
answered
Jun 7, 2023
by
Per Salbark
5.1k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.2m
questions
6.7m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
I need to simplify this expression.
Need answer to math problem!!!
Which property is shown in the problem below? -8(x-3y-9) = -8x+24y+72 A the associative property B the commutative property C the distributive property D the division property ASAP
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org